STUDY OF THE DYNAMICS OF GASEOUS CO2 RELEASE IN A SUPERHEATED WALL LAYER OF C3H6O-CO2 SOLUTION - Ruslan A. Dekhtyar; Valeriy V. Ovchinnikov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2022)
The relevance of the work is caused by the fact that one of the ways to increase the oil recovery factor is using technologies with carbon dioxide as a displacing agent. Emission and absorption of carbon dioxide are the main factors affecting the rate of climate change on Earth. The purpose of the work is to study the features of carbon dioxide evolution in a highly superheated (metastable) layer of a C3H6O-CO2 solution. Object: solution of carbon dioxide CO2 in dimethyl ketone C3H6O. The methods: the method of visualization of gas release in a liquid. To create a layer of a metastable liquid, pulsed heating of a thin wire was carried out. Based on the results of digital processing of photo and video materials, the sizes and shape of the resulting carbon dioxide bubbles and the speed of movement of the boundary of the gas release zone along the wire were determined. It is difficult to distinguish bubbles of gaseous CO2 from vapor bubbles of C3H6O on the frames. Therefore, to separate the data on boiling and gas release, the mass fraction of C3H6O vapors in the vapor-gas cavity was determined from the change in the bubble volume and using the equation of state for CO2 and C3H6O. The results. Depending on the degree of metastability of the near-wall layer of the C3H6O-CO2 solution at pressure in the working volume from 40 to 260 kPa, experimental data were obtained, which made it possible to identify several modes of gas evolution. It is shown that at a low degree of metastability of the near-wall liquid layer, the evolution of gaseous CO2 occurs in the mode of successive chain activation of gas evolution centers. At a high degree of metastability and pressure in the volume of more than 140 kPa, the evolution of gaseous CO2 occurs in the mode of «film gas evolution». For all gas release modes, the rate of movement of the gas release boundary is practically constant in time, but for different gas release modes, the velocity values differ by an order of magnitude.